2001
DOI: 10.1177/014556130108001110
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Inner Ear Disease: Steroid and Cytotoxic Drug Therapy

Abstract: The goal of this study was to assess the effects ofimmun osupp ressiv e therapy on hearing in patients with presumed autoimmune sensorin eural hearin g loss (AISNHL) and a Western blot assay positivefor a 68 kD inner ear antig en. To achieve this objective, we conducted a retrosp ective review of39 such patients who were treated with either a steroid alone or with a steroid followed by a cytotoxic agent. Pure-tone avera ge (PTA) at 500 Hz, 1 kHz, 2 kHz, and 3 kHz and speecli discrimination scores (SDS) were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…A number of case series have described the efficacy of prednisone for treatment of AIED (2,9,19Y21). Of these, only Lasak et al (20) reports detailed side effects for patients treated with steroids alone. In this retrospective case series, 12 patients were treated for a mean total of 3 weeks (range, 2 wk to 3 mo), initially with 1 mg/kg of prednisone or equivalent, followed by taper of unspecified duration.…”
Section: Discussionmentioning
confidence: 99%
“…A number of case series have described the efficacy of prednisone for treatment of AIED (2,9,19Y21). Of these, only Lasak et al (20) reports detailed side effects for patients treated with steroids alone. In this retrospective case series, 12 patients were treated for a mean total of 3 weeks (range, 2 wk to 3 mo), initially with 1 mg/kg of prednisone or equivalent, followed by taper of unspecified duration.…”
Section: Discussionmentioning
confidence: 99%
“…The available data are limited to two retrospective trials and a series of case reports. One trial showed a 57% response rate to cyclophosphamide in patients who initially responded to steroids, but were unable to wean (18), whereas the other showed no difference in outcomes for cyclophosphamide plus steroids, versus steroids alone (17). Given the available data and potentially serious side-effects of this medication, the wisdom of its use remains questionable.…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective study, published in a non-peerreviewed journal, evaluated 62 subjects with clinical AIED and whose Western blot analyses were positive for a 68 kD inner ear antigen (18). Thirty-nine of these patients were considered to have active immune hearing loss and underwent treatment, which included eight with sudden sensorineural hearing loss.…”
Section: Cyclophosphamidementioning
confidence: 99%
See 2 more Smart Citations